"Attention seeker", "drama queen": the power of talk in constructing identities for young people with mental health difficulties. Issue 2 (8th June 2015) - Byrne, Alison; Swords, Lorraine
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Mental health difficulties are often stigmatised because of situated ways of talking that become taken-for-granted "truths". Against this backdrop, identities of those affected are constructed. The purpose of this paper is to explore identities of former inpatients at an Irish Child and Adolescent Mental Health Service. Design/methodology/approach – Ten young people (aged 18-22) participated in discussions and their discourse was analysed using a critical discursive perspective. Findings – Three key identities emerged: a hidden identity, a misunderstood identity and the struggle for a re-claimed identity. Research limitations/implications – Findings indicate the power of discourse in creating stigma and the need for mental health professionals to draw on empowering discourses to help service-users construct positive identities. The importance of involving service-users in research is also implicated. Originality/value – This research involves service-users who are increasingly, although not traditionally, involved in research. Use of qualitative methodology allows their voices to be heard and gives meaning to their experiences.